The effects of the SARS-CoV-2 pandemic on children and youth with special health care needs - Michaud, Mel; Dietz, Irene Cihon (Frontiers in Pediatrics, 2023)
This article seeks to review the current knowledge of the SARS-CoV-2 virus and the health effects for children and youth with special health care needs (CYSHCN). COVID-19, an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), became a major pandemic in 2020. Recognition of the disease could be difficult, as symptoms in children are at times different than adults and can mimic other common childhood viral infections. Children with underlying medical conditions did make up a higher proportion of those hospitalized, but also were affected in other ways including loss of nursing support, missed education and rehabilitative services, and increased stress for themselves and their families, affecting mental health in this vulnerable population. This review seeks to address what is currently known about the overall effects on CYSHCN and their families, and identify gaps in research, including the implementation of health care systems, and possible suggestions for change in the educational and community supports for this group of individuals. Ongoing analysis of large national and international data sets, as well as smaller reports based on specific congenital anomaly, genetics disease, and acquired childhood illness, and then attention to local resources and family resilience is still necessary.